Abdullah Nasih Ulwan: Konsep Pendidikan Seks Bagi Anak - Fadli Padila Putra; Riska Rahmawati (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The focus of this article is to highlight the issue of sex education for children from Abdullah Nasih Ulwan's perspective, with the aim of studying Nasih Ulwan's views and ideas on how sex education is for children themselves. The research method used is literature with the main data source of this research being the book Tarbiyat al-Aulad fi al-Islam by Abdullah Nasih Ulwan. The essence of sex education for children is an attempt to teach children about the organs of the human body and their uses and to prevent children from deviant and incorrect sexual behavior. There are several materials that must be taught to children in relation to sex education, namely; ethics of asking permission, ethics of viewing, keeping children away from things that can stimulate sexuality, ethics of association between the opposite sex, and maintaining self-respect for those who are not married. Nasih Ulwan also explained several strategies that can be used by parents in educating their children about sex education, namely by raising awareness, warning and binding. One thing that is no less important is when educating children, then educate according to their age and educate children according to their era.